Integration of Artificial Intelligence in Database Management Systems for Intelligent Query Processing (International Journal of Food and Nutritional Sciences, 2022)
Finally, in the new age of digitalization, Artificial Intelligence (AI) may have changed how databases are designed, optimized and queried in cooperation with Database Management Systems (DBMS). Conventional methods of DBMS can hardly satisfy the requirements of huge and complicated data, particularly concerning, intelligent query processing. This research paper will examine the applicability of the AI approaches, including machine learning, natural language processing, and deep learning, into the DBMS with a view to optimizing queries, improving performance prediction, and semantic query understanding. The paper also draws attention to the available research, crates a methodological framework, and examines some of the hypothesis regarding the role of AI integration in improving the efficiency of query processing.